DNA Polymorphism of Insulin-like Growth Factor-binding Protein-3 Gene and Its Association with Cashmere Traits in Cashmere Goats - Liu, Haiying (Asian-Australasian journal of animal sciences, 2012)
Insulin-like growth factor binding protein-3 (IGFBP-3) gene is important for regulation of growth and development in mammals. The present investigation was carried out to study DNA polymorphism by PCR-RFLP of IGFBP-3 gene and its effect on fibre traits of Chinese Inner Mongolian cashmere goats. The fibre traits data investigated were cashmere fibre diameter, combed cashmere weight, cashmere fibre length and guard hair length. Four hundred and forty-four animals were used to detect polymorphisms in the hircine IGFBP-3 gene. A 316-bp fragment of the IGFBP-3 gene in exon 2 was amplified and digested with HaeIII restriction enzyme. Three patterns of restriction fragments were observed in the populations. The frequency of AA, AB and BB genotypes was 0.58, 0.33 and 0.09 respectively. The allelic frequency of the A and B allele was 0.75 and 0.25 respectively. Nucleotide sequencing revealed a C>G transition in the exon 2 region of the IGFBP-3 gene resulting in R158G change which caused the polymorphism. Least squares analysis revealed a significant effect of genotypes on cashmere weight (p<0.0001), cashmere fibre length (p<0.001) and hair length (p<0.05) of the animals. The effect of genotypes on cashmere fibre diameter was not statistically significant (p>0.05). The animals of AB and BB genotypes showed higher cashmere weight, cashmere fibre length and hair length than the animals possessing AA genotype. These results suggested that polymorphisms in the hircine IGFBP-3 gene might be a potential molecular marker for cashmere weight in cashmere goats